2015
DOI: 10.1007/s13199-015-0330-6
|View full text |Cite
|
Sign up to set email alerts
|

Validation of candidate reference genes for qRT-PCR studies in symbiotic and non-symbiotic Casuarina glauca Sieb. ex Spreng. under salinity conditions

Abstract: Casuarina glauca is a model actinorhizal plant species that establishes N 2 -fixing symbiosis with Frankia bacteria. This plant is highly resilient to extreme environments, being commonly found in saline zones. Gene expression studies by quantitative real-time polymerase chain reaction (qRT-PCR) constitute a powerful tool to analyze the mechanisms underlying plant stress-tolerance. One of the crucial steps of this technique is the selection and validation of reference genes to produce accurate data. In this wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…The amplification efficiency of each set of primers was confirmed as being higher than 95% according to the standard curve method described by da Costa et al . (2015). Transcript quantification was normalized to Ap47 (Clathrin adaptor complexes subunit) and Act (Actin) as reference genes following the strategy proposed by Vandesompele et al .…”
Section: Methodsmentioning
confidence: 99%
“…The amplification efficiency of each set of primers was confirmed as being higher than 95% according to the standard curve method described by da Costa et al . (2015). Transcript quantification was normalized to Ap47 (Clathrin adaptor complexes subunit) and Act (Actin) as reference genes following the strategy proposed by Vandesompele et al .…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it is essential to screen suitable reference genes in different tissues of H. perforatum under different experimental conditions. Ribosomal RNA and some HKGs are usually used as reference genes, such as actin ( ACT ), tubulin ( TUB) , glyceraldehyde-3-phosphate dehydrogenase ( GAPDH ), and polyubiquitin ( UBQ ) (Costa et al, 2015; Goulao, Fortunato & Ramalho, 2012; Llanos, François & Parrou, 2015; Willems, Leyns & Vandesompele, 2008), whereas many studies have revealed that the most commonly used HKGs are not always reliable among different experimental samples. Thus, an evaluation to screen the optimal HKGs in different species is urgently needed (Ohl et al, 2005; Selvey et al, 2001; Thellin et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…To avoid severe pitfalls in data analysis and interpretation, this implies the selection and systematic validation of suitable reference genes to be used as internal controls. In fact, expression stability should be validated for each particular plant tissue/organ, cell, and experimental conditions, particularly when involving environmental stressful conditions (Die et al, 2010 ; El Kelish et al, 2014 ; Imai et al, 2014 ; da Costa et al, 2015 ). In addition, the stability of reference gene transcripts is also species-dependent (Andersen et al, 2004 ; Gutierrez et al, 2008a , b ), as in the case of coffee (Cruz et al, 2009 ; Goulao et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the stability of reference gene transcripts is also species-dependent (Andersen et al, 2004 ; Gutierrez et al, 2008a , b ), as in the case of coffee (Cruz et al, 2009 ; Goulao et al, 2012 ). A number of housekeeping genes (e.g., b-actin, elongation factor1a, 18S ribosomal RNA, and polyubiquitin) involved in general cell metabolism pathways are widely used to calibrate RT-qPCR studies in biological systems (Willems et al, 2008 ; Goulao et al, 2012 ; Imai et al, 2014 ; da Costa et al, 2015 ; Llanos et al, 2015 ). However, their expression levels may vary with the experimental conditions (Petriccione et al, 2015 ), and their use as internal reference genes should be taken with caution (Gutierrez et al, 2008a , b ).…”
Section: Introductionmentioning
confidence: 99%